The Effects of Pressure Release, Phonophoresis of Hydrocortisone, and Ultrasound on Upper Trapezius Latent Myofascial Trigger Point - Sarrafzadeh, Javad; Ahmadi, Amir; Yassin, Marziyeh (Archives of physical medicine and rehabilitation, 2012)
Sarrafzadeh J, Ahmadi A, Yassin M. The effects of pressure release, phonophoresis of hydrocortisone, and ultrasound on upper trapezius latent myofascial trigger point. To compare the effects of pressure release (PR), phonophoresis of hydrocortisone (PhH) 1%, and ultrasonic therapy (UT) in patients with an upper trapezius latent myofascial trigger point (MTP). Repeated-measure design. A pain control medical clinic. Subjects (N=60; mean±SD age, 21.78±1.76y) with a diagnosis of upper trapezius MTP participated in this study. Subjects were randomly divided into 4 groups: PR, PhH, UT, and control (15 in each group). All patients had a latent MTP in the upper trapezius muscle. PR, PhH, UT. Subjective pain intensity, pain pressure threshold (PPT), and active cervical lateral flexion range of motion were assessed in 6 sessions. All 3 treatment groups showed decreases in pain and PPT and an increase in cervical lateral flexion range of motion ( P<.001) compared with the control group. Both PhH and PR techniques showed more significant therapeutic effects than UT ( P<.001). Our results indicate that all 3 treatments used in this study were effective for treating MTP. According to this study, PhH is suggested as a new method effective for the treatment of MTP.